ABC and HML-methods application for determination and optimization of stock for electrical equipment accessory parts - Beloglazov, A. V.; Rusina, A. G.; Fomenko, O. V.; Pekhota, D. A.; Fyodorova, V. A. (Izvestiâ vysših učebnyh zavedenij. Problemy ènergetiki, 2021)
THE PURPOSE. To describe the use of ABC and HML-methods for predicting the volume of emergency stock for main electrical equipment accessory parts. To describe the content of the methods, consider the problems and complexity of use. To propose an algorithm constructing a new method for forming an emergency stock based on the statistical data of an electric power company. METHODS. Various practical tasks can arise in electric power company. We have determined the most effective method for solving them using a numerical experiment. The highest efficiency of the ABC method is shown. The results of statistical processing will help to improve forecast precision using the ABC-method. RESULTS. The complex of statistical data and ABC-analysis showed high efficiency in short-term forecasting of electrical equipment components emergency stocks. Authors found that HML-analysis provides less precision in predicting the requirement of equipment. CONCLUSION. The ABC method is the most promising for implementation the specific task. The use of the method helps to accurately predict emergency stocks of company electrical equipment. The HML-method does not allow to precision planing the amount of required equipment.